ANALYSIS OF FIRE PROTECTION SYSTEM ON THE MULTIFUNCTIONAL LABORATORY BUILDING OF AR-RANIRY STATE ISLAMIC UNIVERSITY BANDA ACEH INDONESIA - Dedy Ruzwardy; Juliansyah Harahap; Habiyuda Pradana Syahran (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2023)
Fire can occur if three main elements are met, namely heat, oxygen, and fuel or it is called the fire triangle. Risks arising from fire incidents can be minimized by a fire protection system and the reliability of building safety systems. To ensure that the two systems run optimally, an evaluation and examination are needed on the existing conditions based on the applicable safety technical standards. This study aims to determine the existing condition of the applied fire protection system and to determine the reliability of the building safety system in the Ar-Raniry Multifunctional Laboratory Building. This research was conducted using a quantitative descriptive method. Research data collection was carried out using observation and interview methods. The observation method for existing conditions was carried out using a checklist compiled based on the Indonesian Minister Public Works’ Regulation Number 26/PRT/M/2008 of 2008 for fire protection systems and fire protection code from the National Standardization Agency of Indonesia Number Pd-T-11-2005-C on the reliability of building safety systems. The results show that the fire protection system in the UIN Ar-Raniry Multifunction Laboratory building was in the Enough category, with a value of 3.25. This is due to the absence of several active fire protection instruments such as fire extinguishers, sprinklers, and hydrants. Addionally, from the results of the reliability of the building safety system for the UIN Ar-Raniry Multifunction Laboratory building, it is in the Enough category with a value of 63.02. This is caused by the absence of emergency lighting and water sources as a source of hydrant water.